Pengembangan Pondok Pesantren: Islamic Boarding School Development - Cahyadi, Rahmat Arofah Hari (Universitas Muhammadiyah Sidoarjo, 2017)
The development plan of the Islamic Boarding School in the middle of the times it is not impossible to do. As the oldest educational institutions in Indonesia, Islamic Boarding School is an educational institution that is civilized. The development of Islamic boarding school can be done through two aspects; boarding school as an educational unit and boarding school as a place of education units. Islamic Boarding School as an educational unit in the form of Muaddalah Islamic Boarding School while boarding school as a place of education unit is a main unit of doing other educational institutions. Development of the Islamic Boarding School can also be developed through the role of Islamic Boarding Schools that do not merely act as an educational institution, but also serves as a social institutions and economic institutions of society.